Parenting stress in mothers with asthma during the postpartum period. (3rd October 2022) - Mallise, Carly A.; Murphy, Vanessa E.; Karayanidis, Frini; Armstrong, Helen; Whalen, Olivia M.; Woolard, Alix J.; Gibson, Peter G.; Mattes, Joerg; Collison, Adam; Lane, Alison E.; Campbell, Linda E.
Abstract: Objective: Maternal asthma often complicates pregnancy and is linked with poorer quality of life. Additionally, individuals with asthma are at an increased risk of depression and anxiety. We examined whether asthma during pregnancy is related to parenting stress in the first year postpartum and if this relationship varies with level of asthma control. Methods: This cohort survey-based study included mothers with ( n = 157) and without ( n = 79) asthma. Mothers with asthma participated in this study following participation in a randomized controlled trial of a novel asthma management strategy during pregnancy. Mothers completed the Parenting Stress Index – Short Form during the first 12 months postpartum. Mothers with asthma also completed the Asthma Control Questionnaire. Results: Parenting stress did not differ between mothers with and without asthma. Additionally, for mothers with asthma, there were no differences in levels of parenting stress based on asthma control. Conclusions: This study suggests that mothers with asthma are not at an increased risk for excessive parenting stress. However, due to response and sampling bias, levels of parenting stress in asthmatic mothers may be underreported in our sample.